Motivations of Young Adults for Improving Dietary Choices: Focus Group Findings Prior to the MENU GenY Dietary Change Trial. (August 2018) - Alexander, Gwen L.; Lindberg, Nangel; Firemark, Alison L.; Rukstalis, Margaret R.; McMullen, Carmit
Background. Young adulthood is often associated with poor dietary habits that may increase risk of obesity and chronic diseases. As independence grows, little is known about strategies to help balance social, work, and education commitments that may override desires to incorporate healthful food choices. Objective. In advance of a randomized trial to test an online intervention targeting young adults, we sought to identify views and experiences with healthy eating, and specifically, eating more fruits and vegetables. Methods. We conducted 13 focus groups with 68 young adults in metropolitan Detroit (Henry Ford Health System) and rural Pennsylvania (Geisinger Health System). Randomly selected adults aged 21 to 30 years, using health system automated data, were sent recruitment letters. Questions were grounded in social cognitive theory and self-determination theory. Audiotapes were transcribed, content themes identified, coded, verified for reliability, and analyzed qualitatively. Results. Young adults' efforts to eat healthfully included three major themes of (1) motivations to create a healthy lifestyle, teach by example, feel better, and manage weight and future health problems; (2) learning to eat well from childhood, independent living, and peers; and (3) strategies to eat better through planning, tracking, and commitment. Discussion. We uncovered theory-based factors that facilitate healthy dietary behavior change among young adults, including managing their behavior through self-monitoring, goal-setting, small steps, meaningful reinforcements, and social opportunities. Conclusions. Targeted interventions encouraging reflection on personal values related to meaningful contemporary health benefits are likely to resonate with young adults, as will opportunities to receive and share new information.